Systems and computational analysis of gene expression datasets reveals GRB-2 suppression as an acute immunomodulatory response against enteric infections in endemic settings - Naidu, Akshayata; Lulu S., Sajitha (Frontiers in Immunology, 2024)
Introduction: Enteric infections are a major cause of under-5 (age) mortality in low/middle income countries. Although, vaccines against these infections have already been licensed, unwavering efforts are required to boost sub-optimal efficacy and effectiveness in these regions which are highly endemic to enteric pathogens. The role of baseline immunological profiles in influencing vaccine induced immune responses is increasingly becoming clearer for several vaccines. Hence, for the development of advanced and region-specific enteric vaccines, insights into differences in immune responses to perturbations in endemic and non-endemic settings becomes crucial. Material and Methods: For this reason, we employed a two-tiered systems and computational pipeline (i) to study the the variations in differentially expressed genes (DEGs) associated with immune responses to enteric infections in endemic and nonendemic study groups, (ii) to derive features (genes) of importance which keenly distinguish between these two groups using unsupervised machine learning algorithms on an aggregated gene expression dataset. The derived genes were further curated using topological analysis of the constructed STRING networks. The findings from these two tires are validated using multilayer perceptron classifier and were further explored using correlation and regression analysis for the retrieval of associated gene regulatory modules. Results: Our analysis reveals aggressive suppression of GRB-2, an adaptor molecule integral for TCR signalling, as a primary immunomodulatory response against S. typhi infection in endemic settings. Moreover, using retrieved correlation modules and multi-variant regression models we found positive association of regulators of activated T cells and mediators of Hedgehog signalling in the endemic population, which indicates towards the initiation of an effector (involving differentiation and homing) rather inductive response upon infection. On further exploration we found STAT3 to be instrumental in designating T cell functions upon early responses to enteric infections in endemic settings. Conclusion: Overall, through a systems and computational biology approach we characterised distinct molecular players involved in immune responses to enteric infections in endemic settings in the process contributing to the mounting evidence of endemicity being a major determiner of pathogen/vaccine induced immune responses. The gained insights will have important implications in the design and development of region/endemicity-specific vaccines.